A Combined fMRI Study of Typed Spelling and Reading - Purcell, Jeremy J. (2010)
In this study we employed a novel technique to examine the neural basis of written spelling by having subjects touch-type single words on an fMRI compatible QWERTY keyboard. Additionally, in the same group of participants we determined if task-related signal changes associated with typed spelling were also co-localized with or separate from those for reading. Of particular interest were the left inferior frontal gyrus, left inferior parietal lobe as well as an area in the left occipitotemporal cortex termed the Visual Word Form Area (VWFA), each of which have been associated with both spelling and reading. Our results revealed that typed spelling was associated with a left hemisphere network of regions which included the inferior frontal gyrus, intraparietal sulcus, inferior temporal/fusiform gyrus, as well as a region in the superior/middle frontal gyrus, near Exner's area. A conjunction analysis of activation associated with spelling and reading revealed a significant overlap in the left inferior frontal gyrus and occipitotemporal cortex. Interestingly, within the occipitotemporal cortex just lateral and superior to the VWFA we identified an area that was selectively associated with spelling, as revealed by a direct comparison of the two tasks. These results demonstrate that typed spelling activates a predominantly left hemisphere network, a subset of which is functionally relevant to both spelling and reading. Further analysis revealed that the left occipitotemporal cortex contains regions with both conjoint and dissociable patterns of activation for spelling and reading.